The Effect of Temperature on the Rate of Molybdenum Reduction by Enterobacter sp. strain Dr.Y13: Arrhenius Plot Analysis, Temperature Coefficient and Q10 Value Estimation (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2021)
Molybdenum is a micronutrient that is needed a co-factor for many hydroxylation and redox transfer activities in animal and plant physiology. The greatest risk of overexposure is its ability to interfere with the sperm production and egg-production processes in a variety of species, including fish. It is only beginning to be used as a remediation technique for molybdenum-reducing bacteria. Temperature is one of the factors that influence molybdenum reduction. Many models may be used to predict the growth rate of microorganisms on different medium, depending on the temperature. The Arrhenius model is popular because it has few parameters. Temperature generally affects microbial growth and metabolic activity on their substrates. The small nature of microbes makes them susceptible to change in surrounding temperature. Growth on molybdenum by Enterobacter sp. strain Dr.Y13 is described, with a discontinuous chevron-like graph of apparent activation energy with a breakpoint at 32.66 oC. Regression analysis results suggest that in the lower temperature range of 20-30 oC, growth on molybdenum had an activation energy of 62.09 kJ/mol, whereas at the higher temperature range of 37–45 oC, it had an activation energy of 65.05 kJ/mol. For the examined temperature range (20-30 oC) and (37-45 oC), Q10 values of 2.32 and 2.21 and theta values of 1.09 and 1.08 were obtained, respectively. This is study is very useful in predicting the breakdown of molybdenum and the movement of molybdenum during bioremediation.
Keywords: molybdenum-reduction; Enterobacter sp. strain Dr.Y13; Temperature; Arrhenius plot; Breakpoint